The interplay between country image and regional ethnocentrism to motivate students considering neighbouring countries - Hendriana, Evelyn; Awang, Khairil Wahidin; Raja Yusof, Raja Nerina (Palgrave Macmillan, 2023)
Numerous studies of international student decision-making have confirmed the importance of host country and institution images, but these studies tend to run in parallel with country-of-origin research. In the context of regional student mobility, regional ethnocentrism may also play some role. Nevertheless, the interaction between country image and regional ethnocentrism remains untapped. This study aims to examine the relationship between country image and regional ethnocentrism in students interested in studying within a region. The samples of Indonesian middle- and upper-class high school students were selected using the purposive sampling technique. The 431 valid responses were analysed using PLS-SEM to answer the research questions. This study confirmed the interrelationship between the elements of country image. However, only the country’s cognitive image and personality positively affected the institution image, which determined student intention to study in a neighbouring country. Regional ethnocentrism has partially moderated the relationship between the elements of the country brand and institution image. This research gives practical insights to the host country’s government and institutions to effectively design their marketing strategies to target students from neighbouring countries.